Self-Efficacy Training To Improve Hardiness of Firefigthers in “Dinas Kebakaran dan Penanggulangan Bencana Kota Bandung” - Ni Luh Wayan Rai Utari; C.M. Indah Soca R.K; Robert O. Rajagukguk (Universitas Katolik Soegijapranata, 2020)
The purpose of this research is to understand the increasing of hardiness in Firefighter of Dinas Kebakaran dan Penanggulangan Bencana Kota Bandung after given self-efficacy training. The theory used were self-efficacy theory from Bandura (2002) and hardiness from Maddi & Khosaba (2005). The research has 18 subjects as a sample taken by purposive sampling methods. The methods use was Quasi-experimental. Data was analyzed using Wilcoxon signed rank test statistic methods to make comparison between pre-test and post-test. As a result of this research: degree of hardiness in Firefighter of Dinas Kebakaran dan Penanggulangan Bencana Kota Bandung was increase after participate in self-efficacy training. Conclude that self-efficacy training could help to increase hardiness in Firefighter of Dinas Kebakaran dan Penanggulangan Bencana Kota Bandung.